Mechanical characterization of surface modified scaffolds - Koh, Marc Zhen Yang. (2012)
This project is to investigate surface modifications of Polycaprolactone (PCL) scaffold to improve the biocompatibility with human cancellous bone cells. It describes the use of rapid prototyping techniques, focusing on selective laser sintering fabrication. Selective laser sintering uses carbon dioxide laser for powder fusion, without the need for a binder. Prior to fabrication, a design process using Computer-aided Design system, CAD was involved in the project to configure scaffold model. The platform used is Pro/ENGINEER Wildfire with a modular scaffold library, namely Computer Aided System for Tissue Scaffolds (CASTS). By setting parameters in CASTS, desired scaffold design can be obtained.